Distorted body representations in healthy cognition. Issue 3 (4th March 2017) - Longo, Matthew R.
ABSTRACT: Delusions and misperceptions about the body are a conspicuous feature of numerous neurological and psychiatric conditions. In stark contrast to such pathological cases, the immediacy and familiarity of our ordinary experience of our body can make it seem as if our representation of our body is highly accurate, even infallible. Recent research has begun to demonstrate, however, that large and systematic distortions of body representation are a normal part of healthy cognition. Here, I describe this research, focusing on distortions of body representations underlying tactile distance perception and position sense. I also discuss evidence for distortions of higher-order body representations, such as the conscious body image. Finally, I will end with a discussion of the potential relations among different body representations and their distortions.